Evaluation of the Impact of the Watu Ata Nature Reserve Policy Setting - Hendrikus Hironimus Botha; Didik G. Suharto; Rina Herlina Haryanti (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2018)
The major theme of this paper is to evaluate policy impacts. This paper aims to evaluate the impact of the determination of the Watu Ata Nature Reserve using the evaluation criteria proposed by William N. Dunn: Eﬀectiveness, Equity, Responsiveness and Appropriateness. As defined in RI Government Regulation No. 28 of 2011 Article 1, a nature reserve is an area which, due to its natural condition, contains unique plants and/or plant diversity along with natural phenomena and whose ecosystem requires protection and preservation eﬀorts so that its existence and development can grow naturally. The Watu Ata Nature Reserve is one nature reserve area in the Ngada regency based on the Decree of Minister of Forestry No. 432/Kpts-II/92. The research method used is a descriptive qualitative study that employs a field study approach conducted in two villages, namely, Heawea Village and Inelika Village. These two villages have the biggest community’s land in the Watu Ata Nature Reserve. The findings suggest that the Watu Ata Nature Reserve policy has had a negative impact on people living around the nature reserve area, particularly with respect to their loss of access to the cultivated land and cultural sites where they have built relationships with their deceased ancestors.